A systematic review of pregnancy exposure registries: examination of protocol‐specified pregnancy outcomes, target sample size, and comparator selection. Issue 2 (27th December 2016) - Gelperin, Kate; Hammad, Hoda; Leishear, Kira; Bird, Steven T.; Taylor, Lockwood; Hampp, Christian; Sahin, Leyla
Abstract: Purpose: Our study sought to systematically evaluate protocol‐specified study methodology in prospective pregnancy exposure registries including pre‐specified pregnancy outcomes, power calculations for sample size, and comparator group selection. Methods: U.S. pregnancy exposure registries designed to evaluate safety of drugs or biologics were identified fromwww.clinicaltrials.gov, the FDA's Office of Women's Health website, and the FDA's list of postmarketing studies. Protocols or similar documentation were obtained. Results: We identified 35 U.S. registries for drugs or biologic use during pregnancy. All registries assessed risk for overall major congenital malformations. Pre‐specified target enrollment was stated for 18 (51%) registries, and ranged from 150 to 500 exposed pregnancies (median 300). Thirty‐two (91%) registries identified at least one comparison group, but only nine (26%) planned to use an internal comparator. The most common external comparator group ( n  = 24, 69%) was the Metropolitan Atlanta Congenital Defects Program (MACDP). Conclusions: No registries were designed to have sufficient power to assess specific malformations, despite the plausibility that most teratogens cause specific defects. Only half of the registries included a power analysis. Despite their common use, external comparators, including MACDP, have important limitations. In the absence of randomized controlled trial data in pregnant women, pregnancy registries remain an important tool as part of a comprehensive pregnancy surveillance program; however, pregnancy registries alone may not be sufficient to obtain adequate data regarding risks of specific malformations. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.